Simple analytical models for dendrite arm coarsening under high and medium temperature gradients - (:unkn) unknown (Trans Tech Publications Ltd, 2006)
The coarsening of secondary dendrite arms is discussed in terms of two different driving forces, which are the curvature effect and the temperature gradient zone melting (TGZM) effect. It is shown that the driving force due the TGZM effect can be higher than that due to the curvature effect at high temperature gradients and equal to each other at medium temperature gradients. For such high and medium temperature gradients, simple analytical models are proposed to predict the coarsening kinetics of secondary arms during solidification in a binary alloy. The prediction of the present analytical model agrees with experimental data obtained from the solidification of Fe - 1.6 wt.% Mn - 0.75 wt. % C steel.
Keywords: Dendrite arm coarsening; Secondary arm spacing; Solidification of steel; Temperature gradient zone melting (TGZM)